2011
DOI: 10.1002/art.30427
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset neutropenia following rituximab therapy in rheumatic diseases: Association with B lymphocyte depletion and infections

Abstract: Objective. Late-onset neutropenia following rituximab therapy is a well-recognized side effect in lymphoma patients, but only a few cases of late-onset neutropenia have been reported in patients with autoimmune disorders. The purpose of this study was to define the incidence, clinical features, and some of the underlying mechanisms of late-onset neutropenia in relation to rituximab use in several rheumatic diseases.Methods. We conducted a retrospective analysis of a cohort of 209 consecutive patients with rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
1
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 10 publications
14
97
1
13
Order By: Relevance
“…One rheumatology case series noted late-onset neutropenia in 11 of 209 (5%) patients after a median 102 (range, 40-362) days from last rituximab treatment, with higher incidences in patients with AAV and lupus (28). The incidence of neutropenia was 6% in RITUXVAS and 5% in the long-term follow-up of the RAVE trial (specified as $grade 2 leukopenia).…”
Section: Cytopeniasmentioning
confidence: 99%
“…One rheumatology case series noted late-onset neutropenia in 11 of 209 (5%) patients after a median 102 (range, 40-362) days from last rituximab treatment, with higher incidences in patients with AAV and lupus (28). The incidence of neutropenia was 6% in RITUXVAS and 5% in the long-term follow-up of the RAVE trial (specified as $grade 2 leukopenia).…”
Section: Cytopeniasmentioning
confidence: 99%
“…Ob diese generell mit einer erhöhten Infektionsneigung einhergehen, ist nicht eindeutig geklärt [30]. Blutbildverände-rungen wie Leukopenie, Lymphopenie, Neutropenie und Agranulozytose kön-nen unter immunsuppressiver Therapie auftreten [236]. Leukopenien sind ein unabhängiger Risikofaktor für Mortalität bei AAV [138].…”
Section: Blutbild-und Immunglobulinkontrollenunclassified
“…Data in autoimmune rheumatic diseases are more limited and the optimal management of these patients has not been defined. Data from large cohort studies suggested an incidence of 2.5-3.0% in RA, increased to 20% in AAV (33,34). In most cases neutropaenia recovered promptly but counts <0.5 x10 9 /L were associated with severe infection requiring treatment with intravenous antibiotic and granulocyte-colony stimulating factor (GCSF).…”
Section: (Iv) Rituximab-associated Neutropaeniamentioning
confidence: 99%